Perception Meets Reality: A Case Study of Faculty and Student Reflections of Participation in the 2011 World (AIAEE) Conference and Related Activities - Tracy Rutherford (Journal of International Agricultural and Extension Education, 2012)
Students benefit much from participating in international experiences. So too do faculty. The purpose of this qualitative case study was to explore faculty members’ and students’ pre-and post-reflections of participation in the 2011 World (AIAEE) Conference. Seven faculty members (four female and three male faculty members) and six students (three female and three male students; five graduates and one undergraduate) at Texas A&M University were purposefully selected to participate in the study. Respondents recorded their pre-conference reflections about Namibian life, its agricultural systems/practices, and barriers prohibiting participation in international agricultural research or development activities approximately one month before the conference; post-conference reflections were recorded about one month after the conference. Faculty and students alike held similar thoughts about Namibia and her peoples, agricultural systems, and practices during the preflection exercises. Respondents described Namibia as a poverty-stricken, desert-like country where classism existed and agriculture was defined as small-scale, subsistence production practices. Post-conference reflections were changed by the experience; respondents standardized their experiences using their own cultural lenses and U.S.-centric views. Both groups reported time away from family, financial concerns, and language skills as barriers prohibiting international involvement. Future AIAEE conferences in non-U.S. locations should include pre-and post-conference experiences for faculty and students, apart from the conference venue, to broaden participants’ perspectives about life and agricultural systems/practices in the host country
Keywords: Students; Faculty; Experiential Education; Professional Development